(untitled) (British Journal of Global Ecology and Sustainable Development, 2024)
In this article protection of information systems in domains located in the uz domain of the national segment of the Internet network and its levels, the processes of organizing a complex protection system, the tasks of each level, and a model of protection of information systems are proposed.